The Correlation Between Student’s Self-Esteem and English Speaking Ability of Tenth Grade in SMAN 3 Bulukumba - Mardia, Husnatul; Aeni, Nur; Sofyan, Ryan Rayhana (State University of Makassar, 2024)
This research was aimed to know the correlation between student’s self-esteem and English speaking ability of tenth grade in SMAN 3 Bulukumba. This research applies a quantitative method with a pre-experimental research design, where the sample was class 25 students in grade tenth and used simple random sampling. The instrument used questionnaire for the student’s self-esteem and the English speaking ability test. The result of data analysis showed that there are correlation between student’s self-esteem and English speaking ability of tenth grade in SMAN 3 Bulukumba. It can be proven by the result of Pearson Correlation Method that have a significance value (sig) 0.040 < α (0.05). This indicates a rejection of the null hypothesis (H0) and acceptance of the alternative hypothesis (H1). It can be concluded that there are correlations between student’s self-esteem and English speaking ability of tenth grade in SMAN 3 Bulukumba.Key words– Correlation, Student’s Self-esteem, English Speaking Ability